Rheological, thermal and microstructural properties of casein/κ-carrageenan mixed systems. (October 2019) - Tang, Meng-xue; Zhu, Ying-dan; Li, Dong; Adhikari, Benu; Wang, Li-jun
Abstract: The thermal, linear and non-linear rheological as well as microstructural properties of casein/κ-carrageenan mixtures were investigated. The results showed that the addition of κ-carrageenan greatly affected the rheological behavior of casein. The storage ( G′ ) and loss ( G″ ) moduli, and apparent viscosity ( η ) values were positively associated with κ-carrageenan concentration. Casein/κ-carrageenan mixtures showed the typical type Ⅳ (strong strain overshoot) network behavior in the large amplitude oscillatory shear tests. Lissajous plots of casein/κ-carrageenan mixtures appeared stronger nonlinear behavior by adding of κ-carrageenan. The existence of κ-carrageenan also increased the thermal denaturation temperature of casein in the mixture and produced a significant microstructural change within the network entanglements of casein. These changes of casein/κ-carrageenan mixed systems were due to associative interaction between casein and κ-carrageenan caused by electrostatic forces and hydrogen bonding. Graphical abstract: Image 1 Highlights: κ-Carrageenan significantly improves the linear and non-linear rheological, thermal and microstructural properties of casein. Casein/κ-carrageenan mixtures showed typical strong strain overshoot network behavior in LAOS test. Electrostatic interaction and hydrogen bonding occurred between casein and κ-carrageenan.